2023
DOI: 10.1017/s1368980023000137
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SNAP-Ed interventions on California students’ diet and physical activity during COVID-19

Abstract: Objective: School-based CalFresh Healthy Living (CFHL) (California’s SNAP-Ed) interventions adapted to new learning environments necessitated by COVID-19. We examined the impact of these interventions on student diet and physical activity (PA) outcomes. Design: Quasi-experimental, two-group, pre-post. Setting: California public schools with ≥50% of students Free and Reduced Price Meal-eligible (nintervention=47; ncomparison=17). Participants: Fourth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Communities with these characteristics were also at greater risk for COVID-19 infection and complications ( Cantor et al, 2020 ; CDC, 2022 ; Fitzpatrick et al, 2018 ; Hacker et al, 2021 ; Riley et al, 2021 ). Therefore, in the early months of the pandemic, pre-existing health inequities may have been exacerbated by unequal interruptions in SNAP-Ed interventions that improve dietary intake and are associated with improved food security and fitness ( Linares et al, 2023 ; Molitor & Doerr, 2021 ; Rivera et al, 2016 ; Thompson et al, 2020 ). The low R-square values suggest that the measured census-tract characteristics account for a small portion of the observed variation in intervention characteristic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communities with these characteristics were also at greater risk for COVID-19 infection and complications ( Cantor et al, 2020 ; CDC, 2022 ; Fitzpatrick et al, 2018 ; Hacker et al, 2021 ; Riley et al, 2021 ). Therefore, in the early months of the pandemic, pre-existing health inequities may have been exacerbated by unequal interruptions in SNAP-Ed interventions that improve dietary intake and are associated with improved food security and fitness ( Linares et al, 2023 ; Molitor & Doerr, 2021 ; Rivera et al, 2016 ; Thompson et al, 2020 ). The low R-square values suggest that the measured census-tract characteristics account for a small portion of the observed variation in intervention characteristic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated positive SNAP-Ed outcomes including dietary intake, food security, and physical fitness ( Molitor & Doerr, 2021 ; Rivera et al, 2016 ; Thompson et al, 2020 ; Molitor et al, 2015 ). A recent study demonstrated that SNAP-Ed positively impacted dietary outcomes in California schoolchildren during COVID-19 ( Linares et al, 2023 ). The current study examines SNAP-Ed interventions funded through the ( ), and implemented by 60 local health departments (LHDs) in 57 of 58 California counties and three cities thereby reaching millions of Californians each year.…”
Section: Introductionmentioning
confidence: 99%
“…Makaracı et al (2023) concluded in their study that awareness on the positive effect of movement as well as on dietary recommendation is beneficial to students during COVID-19 era. Similarly, Linares et al, (2023) conducted their approach aiming students nutrition and inactivity. Their approach was tailored to the students' attributes regarding nutrition and being active.…”
Section: Theme 4: Needs-based Interventionmentioning
confidence: 99%